A chiral diamine: practical implications of a three‐stereoisomer cocrystallization. Issue 1 (13th December 2017) - Dolinar, Brian S.; Samedov, Kerim; Maloney, Andrew G. P.; West, Robert; Khrustalev, Victor N.; Guzei, Ilia A.
Abstract : The structure resulting from a rare cocrystallization of three stereoisomers, i.e. RR, SS, and meso, of a diamine has been used to compare seven methods for molecular crystal‐volume estimation. Abstract : A brief comparison of seven straightforward methods for molecular crystal‐volume estimation revealed that their precisions are comparable. A chiral diamine, N 2, N 3 ‐bis[2, 6‐bis(propan‐2‐yl)phenyl]butane‐2, 3‐diamine, C28 H44 N2, has been used to illustrate the application of the methods. Three stereoisomers of the diamine cocrystallize in the centrosymmetric space group P 21 / c with Z ′ = 1.5. The molecules occupying general positions are RR and SS, whereas that residing on an inversion center is meso . This is one of only ten examples of three stereoisomers with two asymmetric atoms cocrystallizing together reported to the Cambridge Structural Database (CSD). The conformations of the SS / RR and meso molecules differ considerably and lead to statistically significantly different C(asymmetric)—C(asymmetric) bond lengths in the diastereomers. An advanced Python script‐based CSD searching technique for chiral compounds is presented.